Keabsahan Akta Kuasa Menjual Sebagai Jaminan Atas Perjanjian Hutang Piutang - Khalifa Nur Maulidan (Officium Notarium, 2021)
This paper aims to analyze how the validity of a deed of power of attorney to sell which is used as collateral for a debt agreement which results in deviations from the provisions regarding the application of collateral law, especially in material guarantees, there are two formulation of the problems in this study, first how is the validity of the deed of power of attorney to sell as collateral for a debt agreement accounts receivable? Second, what is the legal protection for debtors and creditors against the power of attorney to sell as collateral? This research is a normative research supported by primary data and secondary data in the form of interviews. The approach used is a statutory approach and is described in a qualitative descriptive manner. The results of this study conclude that, first, that the deed of power of attorney to sell made on the same day with consecutive numbers with the deed of credit agreement is not valid even though it is made by and before the authorized official. Second, a power of attorney to sell does not provide legal protection to creditors or debtors. Legal protection for both parties can actually be by using a material guarantee institution (in the context of this issue the Mortgage guarantee institution)Keywords: Collateral; debt agreement; power of attorney to sellAbstrakTulisan ini bertujuan untuk menganalisis bagaimana keabsahan suatu akta kuasa menjual yang dijadikan jaminan atas perjanjian hutang piutang yang mengakibatkan adanya penyimpangan ketentuan mengenai penerapan hukum jaminan khususnya pada jaminan kebendaan, Terdapat dua rumusan masalah dalam penelitian ini, pertama bagaimana keabsahan akta kuasa menjual sebagai jaminan perjanjian hutang piutang? Kedua, bagaimana perlindungan hukum bagi debitur dan kreditor terhadap kuasa menjual sebagai jaminan? Penelitian ini merupakan penelitian normatif yang didukung dengan bahan hukum (data) primer serta bahan hukum (data) sekunder berupa wawancara. Pendekatan yang digunakan ialah pendekatan perundang-undangan (statue approach) dan diuraikan secara deskriptif kualitatif. Hasil penelitian tesis ini menyimpulkan, pertama, akta kuasa menjual yang dibuat pada hari yang sama dengan nomor yang berurutan dengan akta perjanjian hutang piutang tersebut tidak sah walaupun dibuat oleh dan dihadapan pejabat yang berwenang. Kedua, suatu kuasa menjual tidak memberikan perlindungan hukum kepada pihak kreditor ataupun debitur. Perlindungan hukum untuk kedua belah pihak sejatinya dapat dengan menggunakan lembaga jaminan kebendaan (dalam kontesks persoalan ini lembaga jaminan Hak Tanggungan).Kata Kunci: Akta kuasa menjual; jaminan; perjanjian hutang piutang